Correlation Between Pre-Operative Vitamin D Deficiency and Incidence of Hypocalcemia Following Total Thyroidectomy in Hyperthyroid Patients - Gul Naz, Muhammad Rizwan, Zahid Rasheed, Imran Ali, Natasha Kanwal Mirza, Muhamamd Khurram Jameel, Fawad Hameed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study was designed to determine whether or not "hypocalcemia following complete thyroidectomy in hyperthyroid patients was associated with preoperative vitamin D insufficiency." Methodology: This research was carried out in the West Surgical Ward of Mayo Hospital in Lahore, Pakistan. Total 60 patients were included in the study. Patients were divided in two groups i.e. Vit-D deficient group “with vitamin D deficiency” and Vit-D sufficient group “without vitamin D deficiency”. All the patients underwent total thyroidectomy preserving parathyroid glands performed by the same team of surgeons. Patients were assessed for signs and symptoms of hypocalcemia. Serum calcium was measured at day of surgery, post-operative day-1 and at the end of 2 weeks on follow up after surgery. Results: The mean of age in the Vit-D deficient group was 38.87±9.31 and in Vit-D sufficient group was 37.70±8.56. Majority of patients in the Vit-D deficient group were females (70.0%). In Vit-D deficient group, 13(43.3%) had hypocalcemia, while 5(16.7%) in Vit-D sufficient group (p-value 0.024). Conclusion: Pre-operative VDD “vitamin D deficiency” is linked with postoperative hypocalcemia increased occurrence after total thyroidectomy. There is a “positive correlation of preoperative vitamin D deficiency on postoperative hypocalcaemia after total thyroidectomy in patients of hyperthyroidism”. Keywords: Hyperthyroid, Total Thyroidectomy, Hypocalcemia, Vitamin D deficiency